MIR155HG promotes metastasis and cisplatin resistance of cervical cancer cells by regulating the miR-409-3p and ZEB1 axis - Yanxia Chen; Jing Wang; Youqiang Heng; Yu Guo; Ka Ding; Cailing Ma (Scientific Reports)
Abstract Long non-coding RNA (lncRNA) exhibits a crucial role in multiple human malignancies. The expression of lncRNA MIR155HG, reportedly, is aberrantly up-regulated in several types of tumors. In this research, we studied the role and mechanism of MIR155HG in the progression of cervical cancer (CC). We analyzed the expression pattern of MIR155HG in CC patients using public database TCGA, and overexpressed its expression in HeLa cells to explore its cellular functions. Cellular phenotype experiments were conducted to assess the influence of MIR155HG on HeLa cells, including proliferation, cell cycle, migration, invasion, and cisplatin sensitivity. Then we evaluated the impact on epithelial-mesenchymal transition (EMT) of MIR155HG and identified the underlying regulatory mechanism. We found that MIR155HG was highly expressed and positively correlated with overall survival (OS) prognosis results in CC patients. Overexpression of MIR155HG (MIR155HG-OE) demonstrated higher proliferation and migration levels in HeLa cells, while MIR155HG inhibited the apoptosis rate of HeLa cells. Meanwhile, we found MIR155HG can reduce the effect of cisplatin sensitivity on HeLa cells. Besides this, MIR155HG-OE significantly changed the expression pattern of EMT biomarkers, including ZEB1, TWIST1, Vimentin, N-cadherin, and E-cadherin. To explore the underlying mechanism, we found MIR155HG can promote ZEB1 expression by sponging miR-409-3p, forming a competitive endogenous RNA system to inhibit cisplatin sensitivity. In this study, we deeply explored the molecular and cellular functions of MIR155HG in CC cells. Our results highlight the important role and potential targeting value of MIR155HG in CC pathogenesis and development.